Increasing Knowledge About Patient Safety Culture Among Nurses In Karawang District - Suryani, Lilis (CV. Proaksara Global Transeduka, 2024)
Patient safety culture is an important multidimensional concept in healthcare. Despite efforts to improve safety culture, there are still many preventable medical incidents. Nurses play a vital role in maintaining patient safety due to the intensity and duration of their interactions with patients. This study aims to improve nurses' knowledge of patient safety culture through comprehensive training, so as to reduce adverse events and improve the quality of health services. The training was conducted online on April 5-6, 2024 with 243 participants from various hospitals in Karawang Regency. The activity included pre-test, material delivery, case study simulation, and post-test to measure the participants' knowledge improvement. The results showed that there was a significant increase in nurses' knowledge of patient safety culture after the training. The pre-test and post-test showed that the training was effective in improving nurses' understanding and competence related to patient safety. It can be concluded that the patient safety culture training for nurses is effective and able to improve nurses' knowledge and skills in maintaining patient safety. With this improvement, it is expected that nurses can optimally implement patient safety culture, reduce the risk of adverse events, and improve the quality of health services in hospitals.